(untitled) (Innovation in Woodworking Industry and Engineering design, 2026)
This article deals with the experimental examination of the temperature influence of heat–treated oak wood in terms of quality of the machined surface, as well as analysis of the impact of monitored independent parameters: cutting speed, feed rate, material, angular geometry of the tool, on dependent parameters representing surface treatment quality (Ra – mean arithmetic roughness) in flat milling of thermally modified oak wood (T = 160°C, 180°C, 200°C, 220°C), and their comparison with native wood. The roughness measurement was carried out by non–contact method. Based on experimental measurements, the effect of the observed factors on surface quality was determined in this order: used type of cutting tool, thermal modification, cutting speed, feed rate, rake angle.